Three-Dimensional Modeling of the Behavior of a Blood Clot Using Different Mechanical Properties of a Blood Vessel - Mantas Brusokas; Sergejus Borodinas; Raimondas Jasevičius (Mathematics)
In this work, the behavior of a 3D blood clot located inside a vein under the influence of the mechanical effect of blood flow was analyzed. It has been observed that the mechanical properties of the blood vessel play an important role in the behavior of a blood clot. When the blood vessel changes its shape and/or diameter over time, the position and orientation of the clot in space and time is not constant, and consequently, it influences the blood flow. Moreover, the changed lumen of the blood vessel has a direct impact on the blood velocity, and thus the pressure is exerted not only on the blood vessel wall but also on the thrombus itself. Under these different conditions, it is important to understand the behavior of the blood clot, where each factor with a mechanical influence could potentially lead to clot detachment. Therefore, several variants of numerical simulations were analyzed, including models with different blood vessel properties, considering when the blood vessel wall has (flexible) or does not have (fixed) elastic properties. The results show the blood flow velocity, vessel wall, and blood clot deformations and/or stresses using different vessel wall rigidity levels as well as different blood clot viscoelasticity parameters.